A decade of digital competency: emerging themes and trends - Akti Aslan, Seda; Ayaz, Ahmet; Cekmez, Erdem (Royal Soc, 2026)
This study applies latent Dirichlet allocation (LDA) to analyse 2288 articles on digital competency (DC) from Scopus (2015-2024). It identifies key research themes, tracks their evolution and highlights shifts in research priorities. Fourteen topics emerged, with 'Teacher Education' being the most prominent. Post-COVID-19, DC research surged, with notable growth in 'Scales for Digital Competency Measurement' and 'Higher Education and COVID-19 Digital Transformation'. 'Business and Industry 4.0 Transformation' showed the highest inter-topic acceleration. Conversely, interest in 'Social Media Use' and Psychological Well-Being' declined. Although smaller in volume, the 'Healthcare' theme gained momentum. Visualization revealed thematic clusters around education, business transformation and assessment methods. The findings demonstrate a shift toward emerging fields, reflecting technological advances and evolving societal needs.
Keywords: digital competency; topic modelling; higher education; industry 4.0 transformation; COVID-19 and digitalization